2023
DOI: 10.1002/erv.2994
|View full text |Cite
|
Sign up to set email alerts
|

Watch out! A path from anxiety to anorexia nervosa through biased attention?

Abstract: Objective: Evidence points towards heightened anxiety and attention biases (AB) towards disorder-specific (threatening) stimuli in patients with anorexia nervosa (AN). To date, it is unclear how anxiety and AB interact in eating disorders (ED). The present study tests the causal role of anxiety by inducing anxiety before a dot-probe task with either ED-specific stimuli or unspecific negative (threat-related) information. We expected that anxiety would elicit AB for ED-specific, but not for unspecific threat-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…The presence of more general, non-ED-related biases (that are similar to those found in individuals with other mental disorders such as depression and anxiety; e.g., Mathews & MacLeod, 2005) challenges the assumption that individuals with AN are characterised particularly by content-specific biases, that is, biases for information related to their ED (Williamson et al, 1999). However, only few studies so far have addressed the content-specificity hypothesis by assessing biases for both, ED-related and non-ED-related information within one study (e.g., Hermans et al, 1998;Korn et al, 2020;Radix et al, 2023). Their results indicated biases only for ED-related information, contrasting those of studies investigating biases for non-ED-related information separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of more general, non-ED-related biases (that are similar to those found in individuals with other mental disorders such as depression and anxiety; e.g., Mathews & MacLeod, 2005) challenges the assumption that individuals with AN are characterised particularly by content-specific biases, that is, biases for information related to their ED (Williamson et al, 1999). However, only few studies so far have addressed the content-specificity hypothesis by assessing biases for both, ED-related and non-ED-related information within one study (e.g., Hermans et al, 1998;Korn et al, 2020;Radix et al, 2023). Their results indicated biases only for ED-related information, contrasting those of studies investigating biases for non-ED-related information separately.…”
Section: Introductionmentioning
confidence: 99%
“…An additional limitation of the previous literature is that most studies have been conducted in adults with AN. Studies in adolescents are scarce: Only few studies reported attention biases (e.g., Radix et al, 2023;Sfärlea et al, 2023) and only one study reported negative interpretation biases (for social information; Rowlands et al, 2021) in adolescents with AN compared to adolescents with no mental disorders, despite the facts that (i) the incidence of AN is highest in adolescence (Solmi et al, 2022) and (ii) major cognitive and affective development is ongoing during adolescence (e.g., Steinberg, 2005), making it difficult to transfer results obtained in adult samples on adolescents. As comprehensive knowledge of cognitive biases in adolescents with AN is lacking, the aim of the present study was to systematically investigate whether adolescents with AN show cognitive biases on different levels of information processing and to examine to what extent these biases are specific for ED-related information and to what extent they are general negative biases (content-specificity).…”
Section: Introductionmentioning
confidence: 99%